Resilience and circularity in sustainable building design. ﻿Integrated tools for pre-intervention assessment - Paola De Joanna; Elisabetta Bronzino; Virginia Lusi (Agathón)
The new demands on environmental protection and the energy efficiency of architectural assets open new frontiers to studies for the development of technologies for the control of the building process. The study presented here aims to identify criteria and tools for the control of resilience and circularity factors in construction as moderators of obsolescence processes, capable of stabilizing the construction product in ecosystem growth. The work integrates the results of two ongoing doctoral types of research that address the issue of controlling resilience and circularity in construction as a strategy for reducing environmental impact by identifying specific methodologies for interventions on the built heritage and the digital design process of new buildings.